Renal Artery Microaneurysm in a Woman With Amyloidosis (Iranian Journal of Kidney Diseases, 2016)
Amyloidosis is an extracellular deposition of abnormal serum proteins. Systemic amyloidosis could involve different organs such as the spleen, liver, and kidneys. Renal artery microaneurysm is very rare in renal amyloidosis. We report a 44-year-old woman who was referred to our general hospital for evaluation of rising serum creatinine level, anemia, and pathological fracture. Two hours following renal biopsy, she developed severe pain in the left flank during voiding and ultrasonography revealed a large perinephric hematoma. She underwent angiography that incidentally showed pseudoaneurysm with diffused renal artery microaneurysm. The feeding artery to the pseudoaneurysm was completely ligated by an interventional radiologist. The subsequent histopathological report of the kidney revealed amyloidosis.